Efficient large-scale screening of viral pathogens by fragment length identification of pooled nucleic acid samples (FLIPNAS). Issue 8 (20th March 2023) - Feng, Xianzhen; Zhuang, Xinyu; Lui, Grace; Hsing, I-Ming
Abstract : An assay for the large-scale screening of viral pathogens is reported, named Fragment Length Identification of Pooled Nucleic Acid Samples (FLIPNAS), which is demonstrated to be more cost-effective and efficient than Dorfman-based group testing. Abstract : The necessity for the large-scale screening of viral pathogens has been amply demonstrated during the COVID-19 pandemic. During this time, SARS-CoV-2 nucleic acid pooled testing, such as Dorfman-based group testing, was widely adopted in response to the sudden increased demand for detection. However, the current approach still necessitates the individual retesting of positive pools. Here, we established an efficient method termed the fragment-length identification of pooled nucleic acid samples (FLIPNAS), where all subsamples ( n = 8) can be uniquely labelled and tested in a single-time detection among pools of samples. We used a novel and simple design of unique primers (UPs) to generate amplicons of unique lengths after reverse transcription and polymerase chain reaction to reach this aim. As a result, the unique lengths of the amplicons can be recognized and traced back to the corresponding UPs and specific samples. Our results demonstrated that FLIPNAS could recognize one to eight positive subsamples in a single test without retesting positive pools. The system also showed sufficient sensitivity for the mass monitoring of SARS-CoV-2 and no cross-reactivity against three common respiratory diseases. Moreover, the FLIPNAS results of 40 samples with a positive ratio of 7.8% were in 100% agreement with their individual detection results using the gold standard. Collectively, this study shows that the efficiency of nucleic acid pooling detection can be further improved by FLIPNAS, which can speed up testing and mitigate the urgent demand for resources.